Análisis y evaluación comparativa entre los morteros fabricados en sitio e industrializados, para la empresa Pedregal - Mata-Navarro, Pamela (Instituto Tecnológico de Costa Rica, 2011)
This project focuses on evaluating the physic and mechanic properties of mortars elaborated in the construction place using the tradicional method, including joint mortars and mortars made for covering masonry walls, as well as the properties of the industrialized Multiuso mortars, Pegablock and Repello Grueso, produced by PEDREGAL Company. In order to develop the project, six construction projects with masonry systems were visited, all of them in the surroundings of the province of Cartago. Mortar samples in actual field conditions were taken from each of them, and then they were compared with the results obtained in laboratory tests. Adicionally, it was studied the contribuition of the mortar on the compression strength of the masonry through the manufacture of concrete block prisms, using blocks produced by PEDREGAL company, and joined with traditional, Multiuso and Pegablock mortars. The research concludes by analizing the aplication of the ASTM C-270 norm ("Standar specification for masonry mortars") and it's fulfillment in the field, according to the CSCR-02 code ("Costa Rica Sysmic Code")
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2011.
Keywords: Agregados; Mampostería; Albañilería; Propiedades físicas; Resistencia de materiales; Estructuras de concreto